Front Cover: The Effect of the Phospholipid Bilayer Environment on Cholesterol Crystal Polymorphism (ChemPlusChem 4/2019). Issue 4 (25th February 2019) - Varsano, Neta; Beghi, Fabio; Dadosh, Tali; Elad, Nadav; Pereiro, Eva; Haran, Gilad; Leiserowitz, Leslie; Addadi, Lia
Abstract : The front cover shows how cholesterol crystals form in macrophage cells and in lipid bilayers of different compositions. Stable cholesterol monohydrate triclinic crystals form in vitro as rhomb‐shaped plates, whereas the monoclinic crystals fold into tubular or helical shapes. Which lipid environment favors which polymorph? Do the rods and plates found in atherosclerotic plaques analogously reflect the lipid environment in which the crystals formed? Details are given in the Full Paper by L. Addadi and co‐workers on page 338 in Issue 4, 2019 (DOI: 10.1002/cplu.201800632 ).